Tax Service Quality and Digital Tax Implementation for MSME Tax Compliance in Surabaya - Adhityawati Kusumawardhani; Felix Kristanto Gunawan; Sany Sany; Elisa Tjondro; Tonny Stephanus Eoh (International Journal of Organizational Behavior and Policy, 2024)
This study aims to determine the effect of e-Registration, e-Filing, e-Billing, and Tax Service Quality for MSME (Micro, Small, and Medium Enterprises) Tax Compliance in Surabaya. This study uses multiple linear regression model with a total sample of 150 MSMEs in Surabaya. The results obtained are e-Registration, e-Filing, e-Billing, and tax service quality have a positive effect on tax compliance. This is because taxpayers find it easy to report their taxes with the e-system and also feel good service from tax officials. The findings in this study result in tax compliance with the application of e-Registration, e-Filing, e-Billing, and tax service quality due to the fact that taxpayers are more assisted by system changes in tax reporting. Conversely, this study supports attribution theory which explains that taxpayers can be influenced by their social environment in acting and behaving.